Velours rouge et piquets de grève : la grève du music-hall à Londres en 1907 - John Mullen (Cahiers Victoriens et Edouardiens)
Debate continues about the relationship of music hall culture to the working class. Some emphasize the working class themes of the songs, and the working class origins of the stars. Others consider the role of music hall to be that of a « culture of consolation » perhaps even imposed on workers from above. Writings on the music hall strike in London in 1907 have usually been limited to biographical anecdotes on the role of the stars in the dispute. Our article aims at using the reporting on the strike to examine the situation « behind the scenes » among this rather special group of wage-workers—working conditions and methods of organizing. In particular we will see how the strike contained most of the elements of a classic struggle between workers and their employers, and was treated as such by both sides in the conflict.